2022
DOI: 10.1108/ijqrm-12-2021-0450
|View full text |Cite
|
Sign up to set email alerts
|

The impact of organizational culture and total quality management on the relationship between green practices and sustainability performance

Abstract: PurposeThis study aims to examine the direct and indirect effects of organizational culture (OC) and total quality management practices (TQMPs) on the relationship between green practices (GPs) and sustainability performance (SP) by using structural equation modeling (SEM) analysis.Design/methodology/approachThis study proposed a conceptual research model of the relationships and formulated six hypotheses. This study used a structured questionnaire based on previous studies to collect relationship data to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 81 publications
1
10
0
Order By: Relevance
“…However, the findings indicated that the mediating role of perceived organisational support could strengthen this link. Similarly, Fok et al (2023) strongly supported TQM practices and corporate culture on the TBL dimensions of Sustainability by surveying 441 managers in the US business. Ali AlShehail et al (2022), in an empirical study conducted on the public service sector in the UAE, revealed a positive direct impact of TQM on service innovation and sustainability performance.…”
Section: Qm and Sustainabilitymentioning
confidence: 99%
“…However, the findings indicated that the mediating role of perceived organisational support could strengthen this link. Similarly, Fok et al (2023) strongly supported TQM practices and corporate culture on the TBL dimensions of Sustainability by surveying 441 managers in the US business. Ali AlShehail et al (2022), in an empirical study conducted on the public service sector in the UAE, revealed a positive direct impact of TQM on service innovation and sustainability performance.…”
Section: Qm and Sustainabilitymentioning
confidence: 99%
“…On the other hand, organizational culture and quality management have been claimed to be directly related, being synergic in paving the way for excellence (Fok et al. , 2022a).…”
Section: Research Findingsmentioning
confidence: 99%
“…Implementing effective MDM practices that prioritize environmental sustainability has the potential to establish and strengthen the concept of GC within organizations. According to Fok et al (2023), organizational managers who actively support and incorporate green initiatives into their decision-making processes have the potential to bene t the overall organizational culture. This in uence may lead to the development a green culture that aligns with the organization's sustainability aims.…”
Section: Managerial Decision-making and Green Culturementioning
confidence: 99%